Strengthening True Performance Accountability: Seamless Integration Between Financial Systems and The Cloud to Gain Real-Time Insights into Budget Costs - Kusumba, Surender (The Eastasouth Journal of Information System and Computer Science, 2024)
Strengthening performance accountability has become increasingly important for organizations operating in complex and data-intensive environments, particularly within the energy and utilities sector in the United States. Fragmented financial systems and delayed budget reporting often limit transparency, weaken cost control, and constrain managerial accountability. This study examines how seamless integration between financial systems and cloud-based platforms facilitates genuine performance accountability through real-time budget insights. Adopting a quantitative research design, data were collected from 300 professionals working in finance, accounting, management, and information systems roles within U.S. energy and utilities organizations. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The findings reveal that financial system integration and cloud capability both have significant positive effects on real-time budget insights and true performance accountability. Moreover, real-time budget insights partially mediate the relationships between financial system integration and performance accountability, as well as between cloud capability and performance accountability. These results demonstrate that digital financial infrastructure strengthens accountability most effectively when it generates continuous, real-time budget visibility that supports timely decision-making and transparent financial oversight. This study contributes to the literature on digital finance and performance management by empirically positioning real-time budget insights as a critical mechanism linking cloud-enabled financial integration to accountability outcomes. Practically, the findings offer guidance for organizations seeking to enhance budget transparency and accountability through integrated and cloud-based financial systems.